Private Complaints as a Paradigm Shift: Weaponizing Criminal Law to Enforce the UNCRPD in Punjab Pakistan - Tahir Pervaiz (SOCIAL PRISM, 2026)
Punjab’s disability-rights legislation is often described as a direct route from individual complaint to criminal enforcement. This article tests that claim through a doctrinal reading of the Punjab Empowerment of Persons with Disabilities Act 2022, the Code of Criminal Procedure 1898, the 2024 Rules, the 2025 Monitoring and Enforcement Regulations, the 2026 amendment, and recent constitutional litigation. It develops a six-part ‘complaint-to-consequence’ test: initiator, forum, trigger, proof, consequence, and review. The analysis shows that Punjab has not enacted a general system of direct private criminal prosecution for disability discrimination. It has instead assembled an unfinished enforcement pyramid: district grievance orders and Council appeals at the base; quota, levy, information, and accessibility controls in the regulatory middle; a substantial Council-imposed fine under section 36; and narrowly framed offences before a designated Special Court at the apex. The penal chapter contains a serious procedural discontinuity. Sections 35 and 41 do not clearly connect private-complaint procedure to the Special Court, omit section 37 from the exclusive-cognizance clause, and list section 40 as though it were an offence. Comparison with India’s 2016 Act reveals selective borrowing without express corporate attribution or a Special Public Prosecutor. The article supports criminal escalation for fraud, exploitation, intentional violence, serious obstruction, and repeated wilful defiance, but rejects automatic criminalisation of ordinary discrimination or technical breach. It proposes accessible complaints, remedial orders, anti-retaliation protection, principled corporate liability, and explicit cognizance rules.